2009
DOI: 10.1161/strokeaha.109.563627
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of the Cerebral Cortex Exerts Antiapoptotic, Angiogenic, and Anti-Inflammatory Effects in Ischemic Stroke Rats Through Phosphoinositide 3-Kinase/Akt Signaling Pathway

Abstract: These results suggest that electric stimulation prevents apoptosis through the phosphoinositide 3-kinase pathway. Consequently, the ischemic brain might have been rendered as a nurturing microenvironment characterized by robust angiogenesis and diminished microglial/astrocytic proliferation, resulting in the reduction of infarct volumes and behavioral recovery. Electric stimulation is a novel and potent therapeutic tool for cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 29 publications
5
119
1
1
Order By: Relevance
“…Evidence to support specific mechanisms underlying the effects of open-loop electrical stimulation of the cortex on recovery is largely correlative but includes motor map reorganization, increased dendritic length and spine density, cell proliferation and cell migration in the subventricular zone, receptor subunit expression, activation of antiapoptotic cascades, increased neurotrophic factors, enhanced angiogenesis, and proliferation of inflammatory cells (20,21,(24)(25)(26)(27)(28). Because the number of stimulus pulses was similar in the ADS and OLS groups in the present study, it is reasonable to conclude that if electrical stimulation promoted proliferative processes, the effects were the same in the two groups.…”
Section: Differential Mechanisms Underlying the Effects Of Ols And Admentioning
confidence: 99%
“…Evidence to support specific mechanisms underlying the effects of open-loop electrical stimulation of the cortex on recovery is largely correlative but includes motor map reorganization, increased dendritic length and spine density, cell proliferation and cell migration in the subventricular zone, receptor subunit expression, activation of antiapoptotic cascades, increased neurotrophic factors, enhanced angiogenesis, and proliferation of inflammatory cells (20,21,(24)(25)(26)(27)(28). Because the number of stimulus pulses was similar in the ADS and OLS groups in the present study, it is reasonable to conclude that if electrical stimulation promoted proliferative processes, the effects were the same in the two groups.…”
Section: Differential Mechanisms Underlying the Effects Of Ols And Admentioning
confidence: 99%
“…88,89 There is now mounting evidence that angiogenesis occurs in concert with neurogenesis and synaptogenesis in experimental models of recovery after ischemic brain injury. 90 These processes take place in response to a disparate range of interventions, from cortical stimulation 91 to antidepressant therapy. 92 Although the time course of angiogenesis and neurogenesis overlaps, many investigators have now concluded that the angiogenesis occurs first and leads to axonal remodeling 93 and neuroblast migration along new blood vessels.…”
Section: Stroke and Neovascularizationmentioning
confidence: 99%
“…Striatal stimulation enhances migration of neural progenitor cells towards the penumbra and their subsequent differentiation into neurons [80]. In acute models, cortical stimulation may operate by upregulating neurotrophic and angiogenic factors in tandem with suppression of apoptotic cell death [81]. The ability of stimulation to induce neuroprotection may emerge from its capacity to salvage ischemic tissue, promote neural repair, and/or lower cell death to help sustain gains from rehabilitation-a promise that remains to be substantiated in future.…”
Section: Differentiating Between Short-and Long-term Mechanisms Of Comentioning
confidence: 99%